2007
DOI: 10.1088/1126-6708/2007/07/037
|View full text |Cite
|
Sign up to set email alerts
|

The phase transition and the quasi-normal modes of black holes

Abstract: We reexamined the argument that the quasinormal modes could be a probe of the phase transition of a topological black hole to a hairy configuration by investigating general scalar perturbations. We found further evidence in the quasinormal modes for this phase transition. For the general black hole configurations, we observed that although the quasinormal modes can present us different phases of different configurations, it is not powerful to disclose the phase transition at the critical point.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…In [26], it is suggested that in d = 4, the behaviour of the QNM frequencies slope near this temperature is related to the known phase transition between the topological (hyperbolic) black hole and the MTZ solution (a hyperbolic black hole with scalar hair -see [25], [27]). It is not clear, however, what is the interpretation of such a phase transition in the gauge theory side, and whether the argument extends to higher dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In [26], it is suggested that in d = 4, the behaviour of the QNM frequencies slope near this temperature is related to the known phase transition between the topological (hyperbolic) black hole and the MTZ solution (a hyperbolic black hole with scalar hair -see [25], [27]). It is not clear, however, what is the interpretation of such a phase transition in the gauge theory side, and whether the argument extends to higher dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…But the second moments will diverge when non-extremal black holes become extremal one. Moreover this kind of phase transition may be relevant to the quasinormal modes of black holes [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, the discontinuities observed in the heat capacity of charged Kaluza-Klein black holes with squashed horizons, were connected with the quasi-normal spectrum [22]. Further evidence of a non-trivial relation between the thermodynamical and dynamical properties of black holes was provided in [23].…”
Section: Introductionmentioning
confidence: 99%